Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
This paper presents a novel, geometric interpretation of Supersymmetry (SUSY) within the Helix-Light-Vortex (HLV) framework, offering a solution to the long-standing "superpartner problem." Instead of postulating new fundamental particles, we reinterpret superpartners as dual "spiral phase states" of a single underlying field (Ψ). The transformation between a boson and its fermionic partner is described as a 90-degree rotation (e^(iπ/2)) in a complex phase space, a process geometrically realized as a topological reorientation within the HLV theory's dodecahedral vacuum lattice. The paper introduces a corresponding "spiral super-algebra" with supercharges that govern these phase transitions, linking the symmetry directly to the dynamics of Spiral Time (ψ(t)). This model naturally explains the absence of new particles at the LHC, as superpartners are simply different excitation modes of known particles. Furthermore, it provides new, falsifiable predictions regarding SUSY breaking mechanisms and additional sources of CP violation. Ultimately, this work recasts Supersymmetry from a postulated particle symmetry to an emergent geometric and topological property of a quantized vacuum.
This paper presents a novel, geometric interpretation of Supersymmetry (SUSY) within the Helix-Light-Vortex (HLV) framework, offering a solution to the long-standing "superpartner problem." Instead of postulating new fundamental particles, we reinterpret superpartners as dual "spiral phase states" of a single underlying field (Ψ). The transformation between a boson and its fermionic partner is described as a 90-degree rotation (e^(iπ/2)) in a complex phase space, a process geometrically realized as a topological reorientation within the HLV theory's dodecahedral vacuum lattice. The paper introduces a corresponding "spiral super-algebra" with supercharges that govern these phase transitions, linking the symmetry directly to the dynamics of Spiral Time (ψ(t)). This model naturally explains the absence of new particles at the LHC, as superpartners are simply different excitation modes of known particles. Furthermore, it provides new, falsifiable predictions regarding SUSY breaking mechanisms and additional sources of CP violation. Ultimately, this work recasts Supersymmetry from a postulated particle symmetry to an emergent geometric and topological property of a quantized vacuum.